Development of the Inpatient Dignity Scale Through Studies in Japan, Singapore, and the United Kingdom - Katsumasa Ota; Jukai Maeda; Ann Gallagher; Michiko Yahiro; Yukari Niimi; Moon F. Chan; Masami Matsuda (Elsevier, 2019)
Purpose: The importance of human dignity in care is well-recognized. Care recipients' experiences with undignified care have been reported in many countries. However, few studies have measured these situations quantitatively, especially as there are no tools applicable to inpatients receiving ordinary daily care. This study aimed to develop a valid and reliable Inpatient Dignity Scale (IPDS) that can measure inpatients' expectations of and satisfaction with dignity in daily care. Methods: We conducted a three-phase research project: item generation and a preliminary survey with 47 items related to patients' dignity in Japan, a main survey with 36 items with deliberate translation into English in Singapore, and a confirmatory survey with 35 items in England, with 442, 430, and 500 inpatients as participants in questionnaire surveys, respectively. Data from each survey were processed using factor analysis. Results: Authors obtained a scale with a four-factor structure with acceptable reliability: (F1) respect as a human being, (F2) respect for personal feelings and time, (F3) respect for privacy, and (F4) respect for autonomy. Conclusion: The Inpatient Dignity Scale can be periodically used by hospital administrators or nurses to preserve inpatients' dignity in daily care by monitoring inpatients' views regarding their expectations of and satisfaction with dignity. Keywords: inpatients, nursing, psychometrics, respect